2022
DOI: 10.1590/1980-265x-tce-2022-0206en
|View full text |Cite
|
Sign up to set email alerts
|

From Prenatal to Postpartum Care: Changes in Obstetric Health Services During the Covid-19 Pandemic

Abstract: Objective: to analyze changes in maternal health care during the Covid-19 pandemic, according to reports by health professionals. Method: qualitative research, conducted with managers, physicians, nurses, residents and nursing technicians working in a prenatal outpatient clinic, obstetric emergency department, delivery center and obstetric inpatient ward of a high complexity federal public hospital in the Northeast of Brazil. Data were collected from December 2020 to August 2021. The sample, chosen intentiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies have shown across Brazil persistent gaps related to low coverage, late initiation and the discontinuity of pregnant women attending prenatal consultations, access to diagnosis and treatment centers, in addition to the unpreparedness of health professionals to conduct of quality prenatal care [10][11] . Other studies show, in the same direction, that the quality of prenatal care is directly associated with theoretical-practical intervention approaches, that is, with the expanded and contextualized understanding of biological, psychological and sociocultural aspects by the interprofessional health team [12][13] .…”
Section: Introductionmentioning
confidence: 92%
“…Studies have shown across Brazil persistent gaps related to low coverage, late initiation and the discontinuity of pregnant women attending prenatal consultations, access to diagnosis and treatment centers, in addition to the unpreparedness of health professionals to conduct of quality prenatal care [10][11] . Other studies show, in the same direction, that the quality of prenatal care is directly associated with theoretical-practical intervention approaches, that is, with the expanded and contextualized understanding of biological, psychological and sociocultural aspects by the interprofessional health team [12][13] .…”
Section: Introductionmentioning
confidence: 92%
“…To avoid contamination, practices that valued women's protagonism were neglected, which caused suffering to parturients, family members and professionals. These observed that isolation and the fact of preventing the presence of a companion produced intense suffering in women 4 .…”
Section: /15mentioning
confidence: 98%
“…In April 2020, pregnant and postpartum women were part of the risk group for COVID-19, intensifying protective measures and developing institutional protocols that reorganized obstetric care 3 . In this context, the Brazilian reality was perceived in reduction in the offer of prenatal consultations, in new protocols related to hygiene, in implementation of telecare, in professional burden, in complications for mother and baby due to lack of prenatal care and increased perinatal and fetal mortality 4 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the COVID-19 pandemic exerted a significant impact on the dynamics of maternity-related health services, which resulted in access barriers and difficulties in prenatal, delivery and postpartum follow-up. In addition to that, the environmental and behavioral changes resulting from the pandemic also exerted impacts on the quality of the services provided 34 .…”
Section: /15mentioning
confidence: 99%